UNDERSTANDING MOTIVATION TO DEVELOP MOTIVATIONAL PLAN IN LANGUAGE CLASSROOM: A HINT FOR LANGUAGE TEACHERS - Taufan, Gullit Tornado (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2017)
Motivation is considered as one of the key elements that lead to students’ success in L2 learning. Teacher’s role in building and maintaining motivating atmosphere inside the classroom is undoubtedly crucial. In this case, the teacher should understand what motivation is, how this influences students’ behavior, and what to do to help them motivated.A motivational plan can be developed to help language teacher create and maintain motivating classroom conditions. Regarding this, there are four principle aspects to take into account including: creating the basic motivational conditions, generating initial student motivation, maintaining and protecting motivation, and encouraging positive retrospective self-evaluation.